Prinsip-Prinsip Pendidikan Inklusi Perspektif Al Qur'an - Imaduddin Ahmad, Victor (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
The purpose of this study is to find out the principles of education in the perspective of the Koran. By using the interpretation method maudhu'iy, the results of the study found four principles from the Koran for the implementation of inclusive education. The first principle is compassion as the spiritual capital of the teacher, the second is the nature of differences to get to know each other and learn from one another, third, the value of piety as an indicator of universal glory and fourth Mutual help to others in virtue and piety. From the above study, a common thread can be drawn, that the principles of inclusive education in the study of the interpretation of maudhu'iy are not only of an intellectual technical nature as in the third principle, but also include spiritual aspects that are reflected in the first and third principles, and also social aspects that are reflected in the fourth principle